Pricing Strategies for Each Stage of Product Life Cycle (A Study of Nigeria Bottling Company, Owerri Imo State). (Global Journal of Management and Business Research, 2019)
The price policy definition is one of the most important decisions in management as it affects corporate profitability and market competitiveness. Despite the importance that prices take in organizations, it appears that this element has not received proper attention by many academics and marketers since it represents, according to estimates, less than 2% of the papers on leading journals in the field. Thus, the study determined the pricing strategies for each stage of the product life cycle in NBC Nigeria, specifically Owerri, Imo State. To give direction to the study, four objectives with corresponding research questions and three hypotheses were formulated. Integrating customer value-based pricing strategies, competition-based pricing strategies and cost-based pricing strategies with price levels (high and low) and performance concerning profitability. The results indicate that the profitability of the surveyed companies is positively affected by value-based pricing strategy and high price levels while it is negatively affected by low price levels. Such findings indicate that pricing policies influence the profitability of organizations, and therefore, a more strategic look at the pricing process may constitute one aspect that cannot be overlooked by managers.
Keywords: pricing; strategies; product life cycle